Antihyperalgesic effects of Meteorin in the rat chronic constriction injury model: a replication study. Issue 8 (August 2019) - Xie, Jennifer Y.; Qu, Chaoling; Munro, Gordon; Petersen, Kenneth A.; Porreca, Frank
Abstract : Abstract: Data from preclinical research have been suggested to suffer from a lack of inherent reproducibility across laboratories. The goal of our study was to replicate findings from a previous report that demonstrated positive effects of Meteorin, a novel neurotrophic factor, in a rat model of neuropathic pain induced by chronic constriction injury (CCI). Notably, 5 to 6 intermittent subcutaneous (s.c.) injections of Meteorin had been reported to produce reversal of mechanical allodynia/thermal hyperalgesia after injury, wherein maximum efficacy of Meteorin was reached slowly and outlasted the elimination of the compound from the blood by several weeks. Here, we evaluated the efficacy of Meteorin in reversing hindpaw mechanical hyperalgesia and cold allodynia in male, Sprague-Dawley rats with CCI. Nociceptive behavior was monitored before and after CCI, and after drug treatment until day 42 after injury. Systemic administration of recombinant mouse Meteorin (0.5 and 1.8 mg/kg, s.c.) at days 10, 12, 14, 17, and 19 after CCI produced a prolonged reversal of neuropathic hypersensitivity with efficacy comparable with that obtained with gabapentin (100 mg/kg, orally). Despite some protocol deviations (eg, nociceptive endpoint, animal vendor, testing laboratory, investigator, etc.) being incurred, these did not affect study outcome. By paying careful attention to key facets of study design, using bioactive material, and confirming drug exposure, the current data have replicated the salient findings of the previous study, promoting confidence in further advancement of this novel molecule as a potential therapy for neuropathic pain. Abstract : Careful attention to study design, bioactive material, and drug exposure was used in replication of a single study supporting efficacy of Meteorin in experimental neuropathic pain.